Lippincott's Q & A certification review : emergency nursing (Wolters Kluwer/Lippincott Williams & Wilkins, 2013)
Provides test-taking tips and strategies and an extensive appendix that explores cardiac arrhythmias commonly seen in the ER, ECGs, common life-support drugs, and triage decision making. This book can help you build the expertise to deal with every kind of emergency. It includes abdominal, cardiovascular, environmental, maxillofacial, and medical